Penentuan Prioritas Lokasi Fasharkan TNI AL dengan Metode Fuzzy Analytical Hierarchy Process dan Geographic Information System - Wiyono, Wujud; Thamrin, Suyono; Widodo Putro, Resmanto; Jupriyanto, Jupriyanto (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Based on the regulation of the Navy Chief of Staff No. Per Kasal/39/V/2009 dated May 26, 2009 concerning the development policy of the Navy towards minimum essential force, namely the preparation of the Navy's combat power is directed to achieve minimum essential force or abbreviated as MEF. According to the Chief of Staff of the Navy Number Kep/1771 / XII / 2013 concerning the Administrative Guidebook for the Standardization of TNI AL Bases (PUM-7.03) that a TNI AL Main Base (LANTAMAL) must have a class A Fasharkan, whose ability is to be able to carry out maintenance and repair up to the depot level for all types of KRI, both ship buildings, machinery, sewaco, electricity and ship armaments. There are many studies of location prioritization using the Analytical Hierarchy Process (AHP) method, but the results have uncertainty or decision uncertainty. So this research was conducted using the Fuzzy AHP method to overcome uncertainty or decision uncertainty. The Fuzzy AHP method is used for calculations to select alternatives. After the alternative is selected, then verification of location feasibility is carried out using the Geographic Information System (GIS) display. From the calculation using the FAHP method, Lantamal IX Ambon was selected as an alternative with a weight value of 0.251630342. While verifying the feasibility of the location using GIS, the Tawiri location was chosen as a more feasible land compared to other land options.